Hepatitis A Outbreak Characteristics: A Comparison of Regions with Different Vaccination Strategies, Spain 2010–2018 - Angela Domínguez; Carmen Varela; Núria Soldevila; Conchita Izquierdo; María Guerrero; Marina Peñuelas; Ana Martínez; Pere Godoy; Eva Borràs; Cristina Rius; Núria Torner; Ana María Avellón; et al. (Vaccines, 2021)
We compared the cumulative incidence and characteristics of hepatitis A outbreaks in two groups of Spanish autonomous regions according to whether a universal or risk group vaccination strategy was followed. Outbreaks between 2010 and 2018 were analyzed. The cumulative incidence rate of outbreaks was estimated and compared by estimating the rate ratio (RR). The characteristics of the outbreaks and those of the first cases were compared. Adjusted OR (aOR) were calculated using a multivariate logistic regression model. Outbreak incidence was 16.04 per million persons in regions with universal vaccination and 20.76 in those with risk-group vaccination (RR 0.77; 95%CI 0.62–0.94). Imported outbreaks accounted for 65% in regions with universal vaccination and 28.7% in regions with risk-group vaccination (aOR 3.88; 95%CI 2.13–7.09). Adolescents and young adults aged 15–44 years and men who have sex with men were less frequently the first case of the outbreak in regions with a universal vaccination strategy (aOR 0.54; 95%CI 0.32–0.92 and 0.23; 95%CI 0.07–0.82, respectively). The cumulative incidence rate of outbreaks was lower in regions with universal vaccination. In all regions, independently of the vaccination strategy, activities to vaccinate persons belonging to high-risk groups for infection should be emphasized.